Knowledge, attitude, perception and current practices of health personnel in managing post-stroke delirium in a new stroke centre in Malaysia - Mohd Yosli, Hanin Nabila; Hong, Wei; Khairunnisa Kazura; Abdul Salim, Noor Hafizah; Md Pauzi, Ahmad Luqman; Mat Din, Hazwan; Sallehuddin, Hakimah; Zohari, Zahira; Minhat, Halimatus Sakdiah (Penerbit Universiti Sains Malaysia, 2023)
Introduction: Despite the high prevalence of post-stroke delirium in Malaysia, there are no studies on good practices related to its management. This study aimed to analyse the knowledge, attitude, perception, and factors associated with current practices related to delirium in acute stroke patients among health personnel at Hospital Sultan Abdul Aziz Shah (HSAAS) (formerly known as Hospital Pengajar Universiti Putra Malaysia). Methods: This cross-sectional study was conducted from 26 April 2021 to 9 May 2021 (17 weeks). All health personnel from various departments managing patients with acute stroke in our centre were invited to participate. An online questionnaire was disseminated to assess their knowledge, attitude, perception, and current practices concerning delirium. Multiple logistic regression was used to examine the association between the independent and dependent variables. The level of significance was set at P < 0.05. Results: The response rate was 22.49% (47 of 209 participants). More than half (61.7%, n = 29) had good current practices towards delirium in acute stroke patients. A significant association was found between knowledge and current practices related to delirium (P = 0.024). However, there was no significant association between current practices and sociodemographic factors (age, ethnicity, gender and job position), attitude, perceptions, screening barriers, or health service organisation. Conclusion: Most respondents had good current practices and knowledge in managing post-stroke delirium. Therefore, upskilling health personnel for managing this illness is essential to ensure good post-stroke care and improve prognosis related to delirium.